PERAN PANCASILA DALAM BIDANG PERTANIAN - Sinaga, Alfredo (JOURNAL OF SOCIAL, JUSTICE AND POLICY, 2024)
Pancasila as the basic ideology of the Indonesian state certainly has a very important role in agricultural development. This article aims to examine the role of Pancasila values ​​in agriculture and agricultural innovation to support agriculture in Indonesia. Using literature methods and case analysis, it was found that the implementation of Pancasila values ​​can increase collaboration, sustainability and equal distribution of agricultural products. The research results show that the application of mutual cooperation-based technology and innovation that pays attention to social justice can increase production efficiency and farmer welfare. Pancasila is the foundation of the Republic of Indonesia which has an important role in everyday life. Even though it has a very important role, the implementation of Pancasila values ​​in the agricultural sector still faces various challenges. Some of these are low awareness of the importance of Pancasila values, socio-economic disparities among farmers, and increasingly extreme climate change. Therefore, joint efforts are needed to overcome these challenges and realize dignified and just agriculture.